Ігор Качуровський і Борис Ярхо - Михед, П. (Слово і Час, 2018)
У статті проаналізовані факти інтелектуального і творчого впливу видатного літературознавця
Б. Ярхо на наукові вподобання та інтереси знаного вітчизняного гуманітарія, поета й
перекладача І. Качуровського. Вплив Б. Ярхо, його оригінальне потрактування літератури
європейського Середньовіччя й захоплення перекладами літературних пам'яток не лише
тієї доби – від “Пісні про Роланда” й “Саги про Вельсунгів” до різножанрових творів Мольєра,
Шиллера й Гете позначився на пріоритетах Качуровського-викладача. Кілька чинників на загал
визначили вплив особистості Ярхо на Качуровського: величезна, енциклопедична ерудиція
професора, незалежність думки, лекторський хист, розробка математично достовірних методів
літературознавчого аналізу. Усе це зробило постать Б. Ярхо одним із визначальних топосів
особистісного універсуму Качуровського. The article analyzes and systematizes the facts of creative and personal influence of the outstanding
literary theorist Boris Yarkho on the formation and nature of interests, and preferred research fields of
the well-known Ukrainian philologist, poet and translator Ihor Kachurovskyi. During his student years
at Kursk Pedagogical Institute (1940–1941), Kachurovskyi attended lectures by Yarkho, a politically
oppressed reformer of literary studies, a pioneer of the “exact literary studies”, whose ideas had an
undoubted impact on many philologists of the 20th century. Yarkho, who led the students’ research
work, involved Kachurovskyi in the study of G. Derzhavin’s poetry. Hence, according to the scholar, he
gained an interest in the theoretical issues of poetry, which determined the sphere of Kachurovskyi’s
research work as a professor at the Ukrainian Free University in Munich. Boris Yarkho’s original
understanding and interpretation of European Middle Ages literature, his fascination with translations
of literary texts, not only of that time – from epical “Song of Roland” and the “Völsunga Saga” to the
works of Moliere, Schiller and Goethe, influenced Kachurovskyi’s preferences as a university lecturer.
Polyglot Yarkho (he knew more than 20 languages), still in Kursk, explained the quantitative method
of counting as a precondition for “exact literary studies” and freely used the examples from various
literatures. These activities contributed to subsequent fruitful translation practice and research work
of the former student, who conducted his own studies using a thorough knowledge of 23 languages. The influence of the encyclopedic scholar’s personality turned out to be so powerful that Kachurovskyi got deeply involved in medieval studies and translation of medieval texts. Living in emigration since 1943 and being a university lecturer, Kachurovskyi constantly referred to Yarkho’s ideas preserved in his student notes. He probably did not thoroughly know the methodology of “exact literary studies”, as Yarkho’s fundamental work was published only in 2006, but enthusiastically resorted to all the means of quantitative method in his own scholarly works. Boris Yarkho inspired Kachurovskyi’s idea about the autonomy of poet’s creative pursuits, based on persuasion that a biographical factor does not have a decisive influence on a poet. Kachurovskyi adhered to this idea in his own scholarly historical and literary reflections. In general, several factors determined the impact of Yarkho’s personality on Kachurovskyi: Yarkho’s enormous encyclopedic erudition, independent thinking, the skills of a lecturer, and elaboration of mathematically verified literary analysis. All this made Boris Yarkho’s figure one of the defining topoi of Kachurovskyi’s personal universe.